Antibacterial potential of commercial and wild lactic acid bacteria strains isolated from ovine and caprine raw milk against Mycoplasma agalactiae - Toquet, Marion; Bataller, Esther; Gomis, Jesús; Sánchez, Antonio; Toledo-Perona, Raquel; De la Fe, Christian; Corrales, Juan Carlos; Gómez-Martín, Ángel (Frontiers in Veterinary Science, 2023)
The complexity of fighting contagious agalactia (CA) has raised the necessity of alternative antimicrobial therapies, such as probiotics. Lactic acid bacteria are present in the mammary gland of small ruminants and their antimicrobial effect have been previously described against species like Mycoplasma bovis but never against M. agalactiae. This in vitro study aims to evaluate the antimicrobial activity against Mycoplasma agalactiae (Ma) of ovine and caprine lactic acid bacteria (LAB) strains and a human commercial probiotic (L2) of Lactobacillus spp. A total of 63 possible LAB strains were isolated from nine ovine and caprine farms in Spain, three isolates (33B, 248D and 120B) from the 63 strains were selected, based on their capacity to grow in a specific medium in vitro, for an in vitro experiment to assess their antimicrobial activity against Ma in Ultra High Temperature (UHT) processed goat milk (GM). A women commercial vaginal probiotic was also included in the study. The inoculum of L2 was prepared at a concentration of 3.24 × 108 CFU/mL and the average concentration of the inoculum of the wild LAB varied from 7.9 x 107 to 8.4 x 108 CFU/mL. The commercial probiotic L2 significantly reduced the concentration of Ma to 0.000 log CFU/mL (P < 0.001), strain 33B reduced it from 7.185 to 1.279 log CFU/mL (P < 0.001) and 120B from 6.825 to 6.466 log CFU/mL (P < 0.05). Strain 248D presented a bacteriostatic effect in GM. Moreover, the three wild strains and the commercial probiotic produced a significative reduction of the pH (P < 0.001). This is the first report of the antimicrobial potential of LAB strains against Ma and its interaction. Our results support possible future alternative strategies to antibiotic therapy, previously not contemplated, to fight CA in small ruminants. Further studies are necessary to elucidate the action mechanisms through which these LAB are able to inhibit Ma and to assess the safety of using these strains in possible in vivo studies.